Efforts to Improve Teacher Competence in Making One-Sheet Learning Implementation Plans (RPP) with CLCK Coaching at Min 21 East Jakarta - Mochamad Ansori (International Journal Labs, 2023)
Education is not an easy and simple thing, because, in addition to its complex, dynamic and contextual nature, education is a vehicle for the formation of a person as a whole. This research is qualitative research. This type of research is action research, which is a series of actions that are carried out cyclically in order to solve a problem. Cycle I will take place from August 8, 2022, to August 21, 2022, which consists of several stages, namely: 1) planning stage, 2) implementation stage, 3) the analysis stage, 4) reflection stage. Researchers observed all activities that were in cycle 1, from the planning stage to implementation. CLCK Coaching Model (Example, Exercise, Control, Independent Work) and pat improve teacher competence in making one-sheet RPP (Learning Implementation Plan) at MIN 21 East Jakarta. The provision of coaching / direction and control can streamline the implementation of CLCK coaching. The CLCK Development Model in the preparation of one-sheet RPP is expected to be implemented on an ongoing basis and have a positive impact on learning outcomes in the classroom.